Corrosion-resistant photosensitive dry film and preparation method thereof

CN123010335APending Publication Date: 2026-10-30SHAOGUAN YUANWANG COATING FACTORY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611301229.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0022]本发明通过在丙烯酸树脂体系中添加功能填料,其制备过程中油酸改性和核壳结构增韧相容剂的添加,都对干膜性能的提升起到了明显的正向作用,经过两步改性处理得到的功能填料,能够均匀稳定地分散在感光树脂基体中,有效改善了干膜整体的耐腐蚀与力学性能,满足高精度线路制作对感光干膜耐腐蚀性能的使用要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a corrosion-resistant photosensitive dry film and a preparation method thereof, and belongs to the technical field of photosensitive dry film materials. The corrosion-resistant photosensitive dry film is processed from a photosensitive resin composition, and the photosensitive resin composition comprises the following components: an acrylic resin, a photopolymerization monomer, a functional filler and a photoinitiator. The functional filler obtained through two-step modification treatment is uniformly and stably dispersed in the photosensitive resin matrix, the corrosion resistance and the mechanical properties of the dry film as a whole are effectively improved, and the use requirement of the photosensitive dry film corrosion resistance for high-precision line production is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of photosensitive dry film materials, and relates to a corrosion-resistant photosensitive dry film and its preparation method. Background Technology

[0002] Photosensitive dry film is a crucial photosensitive material in printed circuit board (PCB) manufacturing. With the continuous development of the electronics industry, PCBs are upgrading towards higher density and higher precision, placing higher demands on the performance of photosensitive dry film. During its use, photosensitive dry film undergoes acidic or highly corrosive processes such as etching and copper plating. The dry film must withstand the erosion of the etching solution to ensure the integrity and clarity of the manufactured circuitry and avoid defects such as circuit deformation, broken lines, and excessive lateral etching. Summary of the Invention

[0003] The purpose of this invention is to provide a corrosion-resistant photosensitive dry film and its preparation method. Using acrylic resin as the matrix, functional fillers prepared by special two-step modification are added to improve the compatibility between the fillers and the resin matrix, so that they are uniformly and stably dispersed in the system, effectively improving the corrosion resistance and mechanical properties of the prepared photosensitive dry film, and meeting the requirements of high-precision printed circuit board circuit manufacturing.

[0004] The technical solution adopted by this invention to solve its technical problem is:

[0005] A corrosion-resistant photosensitive dry film is prepared by coating and drying a photosensitive resin composition, wherein the photosensitive resin composition comprises the following components in parts by weight:

[0006] Acrylic resin 100-115 parts, photopolymerizable monomer 14-20 parts, functional filler 2.8-4.0 parts, photoinitiator 2-5 parts.

[0007] Furthermore, the present invention modifies silica by first grafting double bonds with silane, then grafting oleic acid with UV initiation, and finally performing melt extrusion modification with a compatibilizer. The resulting functional filler can significantly improve its compatibility with the acrylic resin matrix, prevent filler agglomeration, and ultimately significantly improve the corrosion resistance and mechanical stability of the dry film.

[0008] As a preferred embodiment of the present invention, the acrylic resin is selected from Keding MR2402.

[0009] As a preferred embodiment of the present invention, the photopolymerizable monomer is composed of tripropylene glycol diacrylate and pentaerythritol tetraacrylate.

[0010] Furthermore, the photopolymerizable monomer is composed of tripropylene glycol diacrylate and pentaerythritol tetraacrylate in a mass ratio of 3:1. The combination can improve the flexibility and resolution of the dry film while ensuring the crosslinking density after curing, thus meeting the needs of fine circuit fabrication.

[0011] The preparation of the functional filler includes the following steps:

[0012] S1. Disperse dry silica powder in a solvent, add silane coupling agent and reflux reaction, take filter cake, wash, and vacuum dry to obtain silane modified silica.

[0013] S2. Under nitrogen protection, silane-modified silica, oleic acid and anhydrous ethanol are ultrasonically dispersed, a photoinitiator is added and irradiated with ultraviolet light, the solid is filtered out, washed and vacuum dried to obtain intermediate filler.

[0014] S3. Melt and extrude the intermediate filler and additives, cool and granulate to obtain the functional filler.

[0015] As a preferred embodiment of the present invention, the silica powder in step S1 is of type SBA-15, the reflux reaction conditions are reflux at 70-75°C for 5-6 hours, the washing is washing with anhydrous ethanol 3 times, and the vacuum drying is vacuum drying at 60-65°C to constant weight.

[0016] As a preferred embodiment of the present invention, the ratio of silica powder, solvent and silane coupling agent in step S1 is 15-18g: 100-110mL: 5.0-6.5g, and the solvent is anhydrous ethanol.

[0017] As a preferred embodiment of the present invention, the ultrasonic dispersion time in step S2 is 30-45 min, the washing is washing with anhydrous ethanol 3 times, the vacuum drying conditions are vacuum drying at 80°C to constant weight, and the ultraviolet lamp irradiation conditions are irradiation with an ultraviolet lamp at a wavelength of 365 nm for 4-5 h.

[0018] As a preferred embodiment of the present invention, the ratio of silane-modified silica, oleic acid and anhydrous ethanol in step S2 is 12-14g: 2.5-3.0g: 50-60mL.

[0019] As a preferred embodiment of the present invention, the temperature of the melt extrusion in step S3 is 170-190°C, the mass ratio of the intermediate filler to the additive is 18-20:1.0-1.3, and the additive is a core-shell toughening compatibilizer, Jia Yi Rong® SBG-001.

[0020] A method for preparing a corrosion-resistant photosensitive dry film includes the following steps: coating and drying a photosensitive resin composition sequentially.

[0021] The beneficial effects of this invention are:

[0022] This invention adds functional fillers to an acrylic resin system. During the preparation process, the addition of oleic acid modification and core-shell toughening compatibilizers have a significant positive effect on improving the performance of the dry film. The functional fillers obtained through two-step modification can be uniformly and stably dispersed in the photosensitive resin matrix, effectively improving the overall corrosion resistance and mechanical properties of the dry film, and meeting the requirements of high-precision circuit fabrication for the corrosion resistance of photosensitive dry films. Detailed Implementation

[0023] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.

[0024] Example 1

[0025] A corrosion-resistant photosensitive dry film is prepared by coating and drying a photosensitive resin composition, wherein the photosensitive resin composition comprises the following components in parts by weight:

[0026] 100 parts acrylic resin, 14 parts photopolymerizable monomer, 2.8 parts functional filler, and 2 parts photoinitiator;

[0027] The acrylic resin is selected from Keding MR2402, the photopolymerizable monomer is composed of tripropylene glycol diacrylate and pentaerythritol tetraacrylate in a mass ratio of 3:1, and the photoinitiator is photoinitiator 1173.

[0028] The preparation of the functional filler includes the following steps:

[0029] S1. Disperse the dry silica powder in anhydrous ethanol solvent, add silane coupling agent and reflux at 70°C for 5 hours. Take the filter cake and wash it three times with anhydrous ethanol. Dry it under vacuum at 60°C to constant weight to obtain silane-modified silica.

[0030] The silica powder is of type SBA-15, and the ratio of silica powder, solvent and silane coupling agent is 15g:100mL:5.0g; the silane coupling agent is of type KH580.

[0031] S2. Under nitrogen protection, silane-modified silica, oleic acid and anhydrous ethanol were ultrasonically dispersed for 30 min. Photoinitiator 1173 was added and the mixture was irradiated with a UV lamp at a wavelength of 365 nm for 4 h. The solid was filtered out, washed three times with anhydrous ethanol, and dried under vacuum at 80 °C to constant weight to obtain the intermediate filler.

[0032] The ratio of silane-modified silica, oleic acid, and anhydrous ethanol is 12g:2.5g:50mL.

[0033] S3. The intermediate filler and additives are melt-extruded at 170°C, cooled, and granulated to obtain the functional filler.

[0034] The mass ratio of the intermediate filler to the additive is 18:1.0, and the additive is a core-shell toughening compatibilizer, Jia Yi Rong® SBG-001.

[0035] A method for preparing a corrosion-resistant photosensitive dry film includes the following steps: coating and drying a photosensitive resin composition sequentially.

[0036] Example 2

[0037] A corrosion-resistant photosensitive dry film is prepared by coating and drying a photosensitive resin composition, wherein the photosensitive resin composition comprises the following components in parts by weight:

[0038] 108 parts acrylic resin, 17 parts photopolymerizable monomer, 3.4 parts functional filler, and 4 parts photoinitiator;

[0039] The acrylic resin is selected from Keding MR2402, the photopolymerizable monomer is composed of tripropylene glycol diacrylate and pentaerythritol tetraacrylate in a mass ratio of 3:1, and the photoinitiator is photoinitiator 1173.

[0040] The preparation of the functional filler includes the following steps:

[0041] S1. Disperse the dry silica powder in anhydrous ethanol solvent, add silane coupling agent and reflux at 72°C for 5.5 h, take the filter cake and wash it 3 times with anhydrous ethanol, and dry it under vacuum at 62°C to constant weight to obtain silane modified silica.

[0042] The silica powder is of type SBA-15, and the ratio of silica powder, solvent and silane coupling agent is 16g:105mL:5.8g; the silane coupling agent is of type KH580.

[0043] S2. Under nitrogen protection, silane-modified silica, oleic acid and anhydrous ethanol were ultrasonically dispersed for 38 min. Photoinitiator 1173 was added and the mixture was irradiated with a UV lamp at a wavelength of 365 nm for 4.5 h. The solid was filtered out, washed three times with anhydrous ethanol, and dried under vacuum at 80 °C to constant weight to obtain the intermediate filler.

[0044] The ratio of silane-modified silica, oleic acid, and anhydrous ethanol is 13g:2.8g:55mL.

[0045] S3. The intermediate filler and additives are melt-extruded at 180°C, cooled, and granulated to obtain the functional filler.

[0046] The mass ratio of the intermediate filler to the additive is 19:1.2, and the additive is a core-shell toughening compatibilizer, Jia Yi Rong® SBG-001.

[0047] A method for preparing a corrosion-resistant photosensitive dry film includes the following steps: coating and drying a photosensitive resin composition sequentially.

[0048] Example 3

[0049] A corrosion-resistant photosensitive dry film is prepared by coating and drying a photosensitive resin composition, wherein the photosensitive resin composition comprises the following components in parts by weight:

[0050] 115 parts acrylic resin, 20 parts photopolymerizable monomer, 4.0 parts functional filler, and 5 parts photoinitiator;

[0051] The acrylic resin is selected from Keding MR2402, the photopolymerizable monomer is composed of tripropylene glycol diacrylate and pentaerythritol tetraacrylate in a mass ratio of 3:1, and the photoinitiator is photoinitiator 1173.

[0052] The preparation of the functional filler includes the following steps:

[0053] S1. Disperse the dry silica powder in anhydrous ethanol solvent, add silane coupling agent and reflux at 75°C for 6 hours. Take the filter cake and wash it 3 times with anhydrous ethanol. Dry it under vacuum at 65°C to constant weight to obtain silane-modified silica.

[0054] The silica powder is of type SBA-15, and the ratio of silica powder, solvent and silane coupling agent is 18g:110mL:6.5g; the silane coupling agent is of type KH580.

[0055] S2. Under nitrogen protection, silane-modified silica, oleic acid and anhydrous ethanol were ultrasonically dispersed for 45 min. Photoinitiator 1173 was added and the mixture was irradiated with a UV lamp at a wavelength of 365 nm for 5 h. The solid was filtered out, washed three times with anhydrous ethanol, and dried under vacuum at 80 °C to constant weight to obtain the intermediate filler.

[0056] The ratio of silane-modified silica, oleic acid, and anhydrous ethanol is 14g:3.0g:60mL.

[0057] S3. The intermediate filler and additives are melt-extruded at 190°C, cooled, and granulated to obtain the functional filler.

[0058] The mass ratio of the intermediate filler to the additive is 20:1.3, and the additive is a core-shell toughening compatibilizer, Jia Yi Rong® SBG-001.

[0059] A method for preparing a corrosion-resistant photosensitive dry film includes the following steps: coating and drying a photosensitive resin composition sequentially.

[0060] Comparative Example 1

[0061] Compared to Example 3, Comparative Example 1 did not use oleic acid, but was otherwise the same as Example 3.

[0062] Comparative Example 2

[0063] Compared with Example 3, Comparative Example 2 did not use any additives, but was otherwise the same as Example 3.

[0064] Comparative Example 3

[0065] Compared with Example 3, Comparative Example 3 used silica powder instead of functional filler, and was otherwise the same as Example 3.

[0066] The membrane samples prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the following performance tests, and the test results are shown in Table 1.

[0067] Acid resistance: First, immerse the cured film in a 10wt% H2SO4 aqueous solution at 25℃ for 30 minutes. After that, wipe the water stains on the film surface with a lint-free cloth, then use a cross-cutting tool to make a grid on the film surface, and then pull it up vertically at 90° with 3M 600 tape.

[0068] Alkali resistance: First, immerse the cured film in a 10 wt% NaOH aqueous solution at 25℃ for 30 minutes. After that, wipe the water stains on the film surface with a lint-free cloth, then use a cross-cutting tool to make a grid on the film surface, and then pull it up vertically at 90° with 3M 600 tape.

[0069] Tensile strength: GB / T 1040.3-2018.

[0070] Table 1

[0071]

[0072] As can be seen from the test results in Table 1, Examples 1-3 and Comparative Examples 1-3 show that...

[0073] The corrosion-resistant photosensitive dry film prepared by this invention has superior mechanical strength and acid and alkali corrosion resistance.

[0074] This invention utilizes the silane coupling agent KH580 to hydrolyze and bond hydroxyl groups on the silica surface, while simultaneously introducing thiol functional groups to functionalize the silica surface and construct active sites capable of undergoing thiol-ene reactions. Subsequently, a photo-initiated thiol-ene click reaction is initiated through the carbon-carbon double bond between the thiol and oleic acid, grafting flexible long-chain oleic acid onto the inorganic silica surface to form a flexible organic bridging layer, alleviating inorganic-organic interfacial stress and improving interfacial compatibility. Finally, the use of Jia Yi Rong® SBG-001 core-shell compatibilizer for melt blending further optimizes interfacial bonding, toughens the matrix, and reduces microscopic crack defects in the cured film. The overall structure forms a covalently bonded inorganic-organic composite structure that retains the labyrinth barrier corrosion resistance of silica while eliminating interfacial crevice corrosion channels, improving cross-linking density and toughness, thereby significantly improving the overall acid and alkali corrosion resistance and mechanical properties of the photosensitive dry film.

[0075] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A corrosion-resistant photosensitive dry film, prepared from a photosensitive resin composition, characterized in that, The photosensitive resin composition comprises the following components in parts by weight: 100-115 parts acrylic resin, 14-20 parts photopolymerizable monomer, 2.8-4.0 parts functional filler, and 2-5 parts photoinitiator.

2. The corrosion-resistant photosensitive dry film according to claim 1, characterized in that: The photopolymer monomer is composed of tripropylene glycol diacrylate and pentaerythritol tetraacrylate.

3. A method for preparing a corrosion-resistant photosensitive dry film as described in any one of claims 1-2, characterized in that, The preparation method includes the following steps: coating and drying the photosensitive resin composition sequentially.

4. The method for preparing a corrosion-resistant photosensitive dry film according to claim 3, characterized in that, The preparation of the functional filler includes the following steps: S1. Disperse dry silica powder in a solvent, add silane coupling agent and reflux reaction, take filter cake, wash, and vacuum dry to obtain silane modified silica. S2. Under nitrogen protection, silane-modified silica, oleic acid and anhydrous ethanol are ultrasonically dispersed, a photoinitiator is added and irradiated with ultraviolet light, the solid is filtered out, washed and vacuum dried to obtain intermediate filler. S3. Melt and extrude the intermediate filler and additives, cool and granulate to obtain the functional filler.

5. The method for preparing a corrosion-resistant photosensitive dry film according to claim 3, characterized in that: The silica powder mentioned in step S1 is of type SBA-15.

6. The method for preparing a corrosion-resistant photosensitive dry film according to claim 3, characterized in that: The reflux reaction conditions are reflux at 70-75℃ for 5-6 hours, and the ratio of silica powder, solvent and silane coupling agent is 15-18g: 100-110mL: 5.0-6.5g.

7. The method for preparing a corrosion-resistant photosensitive dry film according to claim 3, characterized in that: The conditions for ultraviolet irradiation in step S2 are to irradiate with an ultraviolet lamp at a wavelength of 365nm for 4-5 hours, and the ratio of the amount of silane-modified silica, oleic acid and anhydrous ethanol is 12-14g: 2.5-3.0g: 50-60mL.

8. The method for preparing a corrosion-resistant photosensitive dry film according to claim 3, characterized in that: The melt extrusion temperature in step S3 is 170-190℃, and the mass ratio of the intermediate filler to the additive is 18-20: 1.0-1.3, the additive is a core-shell structure toughening compatibilizer.